2022
DOI: 10.1101/2022.07.23.501214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EvoBind: in silico directed evolution of peptide binders with AlphaFold

Abstract: Currently, there is no accurate method to computationally design peptide binders towards a specific protein interface using only a target structure. Experimental methods such as phage display can produce strong binders, but it is impossible to know where these bind without solving the structures. Using AlphaFold2 (AF) and other AI methods to distinguish true binders has proven highly successful but relies on the availability of binding scaffolds. Here, we develop EvoBind, an in silico directed-evolution platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Accordingly, we found that our cRBM model better predicted binding affinity changes upon mutation that ProteinMPNN [58], a recently published structure-based autoregressive graph neural network for sequence design. Synergy between evolutionary-based and structure-based protein design approaches is well-established [68][69][70][71] and therefore, although structure-based computational design methods are rapidly improving [58,72,73], we expect that evolutionary information will still prove valuable in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we found that our cRBM model better predicted binding affinity changes upon mutation that ProteinMPNN [58], a recently published structure-based autoregressive graph neural network for sequence design. Synergy between evolutionary-based and structure-based protein design approaches is well-established [68][69][70][71] and therefore, although structure-based computational design methods are rapidly improving [58,72,73], we expect that evolutionary information will still prove valuable in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The scope of machine learning applications has expanded dramatically within the past three years and accelerated the prediction of protein structures. The advent of Alpha-Fold ( 22 ) has recently been harnessed by others to create in silico models for designing binding reagents for any interface ( 24 ). It will be interesting to follow the development of such approaches and compare the experimental validation data accompanying computational classification schemes.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of Alpha-Fold (22) has recently been harnessed by others to create in silico models for designing binding reagents for any interface (24). It will be interesting to follow the development of such approaches and compare the experimental validation data accompanying computational classification schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Note that we do not necessarily expect the receptor to have the top rank -many peptides are known to have more than one endogenous binding partner [6]. Moreover, the exact ordering of receptors by AlphaFold confidence is unlikely to correlate to binding strength [19]. However, with respect to a full receptor library, any true receptor can still be expected to rank high.…”
Section: Methodsmentioning
confidence: 97%